219k views
2 votes
Y= 5x -7 -3x -2y= -12

User Ravi Ojha
by
5.2k points

1 Answer

7 votes

y=5x-7
-3x-2y=-12

To find the solutions by substitution:

1. Clear a variable (x or y) in one of the equations:

As in the first equation the variable y is clear you don't need to clear a variable.

2. Substitute the value of the clear variable in the other equation:


-3x-2(5x-7)=-12

3. Make operations:


-3x-10x+14=-12
-13x+14=-12

4. Clear the variable x:

5. Subtitute the value of the x in the first equation to find the value of y:


y=5(2)-7
y=10-7=3

----------------------------

Then so, the value of the variables in the given system of equations is:y=3x=2
Y= 5x -7 -3x -2y= -12-example-1
Y= 5x -7 -3x -2y= -12-example-2
User Nimish Bansal
by
4.3k points